2022
DOI: 10.3168/jds.2022-21922
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of production-related responses to hyperinsulinemia and hypoglycemia induced by clamp procedures or heat stress of lactating dairy cattle

Abstract: Hyperinsulinemia concurrent with hypoglycemia is one of a myriad of physiological changes typically experienced by lactating dairy cows exposed to heat stress, the consequences of which are not yet well defined or understood. Therefore, the objective of this experiment was to separate the production-related effects of hyperinsulinemia with hypoglycemia from those of a hyperthermic environment. Multiparous lactating Holstein cows (n = 23; 58 ± 4 d in milk, 3.1 ± 0.3 lactations) were housed in temperature-contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Cow respiration rates and rectal temperatures are reported in a previous paper, and were both significantly increased during HS periods compared to TN periods [ 17 ]. Milk yield, components, and somatic cell count in cows maintained under thermoneutral and heat stress conditions are presented Table 2 .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Cow respiration rates and rectal temperatures are reported in a previous paper, and were both significantly increased during HS periods compared to TN periods [ 17 ]. Milk yield, components, and somatic cell count in cows maintained under thermoneutral and heat stress conditions are presented Table 2 .…”
Section: Resultsmentioning
confidence: 96%
“…This experiment utilized a subset of samples from a previous study [ 17 ] and complete experimental details can be found in that paper. All procedures involving animals were approved by the Virginia Tech Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, blood glucose concentrations in the current experiment did not differ between treatment groups ( Table 1 ). Previous work from our laboratory and others suggests that insulin-stimulated glucose uptake is already maximized in heat-stressed dairy cattle ( Rhoads et al, 2009 ; Xie et al, 2016 ; Stewart et al, 2022 ). Consequently, it is likely that Cr is unable to further increase glucose uptake under these conditions.…”
mentioning
confidence: 78%